2010
DOI: 10.1007/s00586-010-1288-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single dose of pamidronate administered at the time of surgery in a rabbit posterolateral spinal fusion model

Abstract: Spinal fusion is usually performed on patients who receive bisphosphonates (BP); however, limited data on their action on spinal fusion are available. Previous studies in animal models have shown that chronic administrations of BP reduced spinal fusion rates, and only one study has shown that a single dose administration of zolendronic acid increased fusion rate. The objective of the present study was to evaluate if pamidronate (PA), which was previously demonstrated to reduce spinal fusion rate when administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
4
0
1
Order By: Relevance
“…The aim of this study was to achieve a fusion rate of less than 40 % and then determine whether autologous bone marrow augmented arthrodesis. Other studies subsequently used this bone paucity model to provide a larger potential for improved fusion rates with a variety of bone graft substitutes [13][14][15][16][17][18][19][20][21][22]. While our study found a significant positive relationship between volume of autograft and fusion rates, a tenfold range of volume of autograft (1.4-12 cm 3 ) was used in the studies evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…The aim of this study was to achieve a fusion rate of less than 40 % and then determine whether autologous bone marrow augmented arthrodesis. Other studies subsequently used this bone paucity model to provide a larger potential for improved fusion rates with a variety of bone graft substitutes [13][14][15][16][17][18][19][20][21][22]. While our study found a significant positive relationship between volume of autograft and fusion rates, a tenfold range of volume of autograft (1.4-12 cm 3 ) was used in the studies evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…For this reason, longer instrumented fusions that span the entire thoracic spine are often needed. The role of bisphosphonates in spinal fusion is controversial in the literature with some reports suggesting inhibition of fusion, while others state the opposite [34][35][36][37][38][39][40][41][42][43][44][45][46]. In contrast, both animal and clinical studies seem to suggest that teriparatide [recombinant human parathyroid hormone (rhPTH)] enhances fusion [47][48][49][50].…”
Section: Suggestions To Minimize Pjkmentioning
confidence: 88%
“…This dose in rats is equivalent to 250 mg in a 70 kg human [25]. The pamidronate infusion dose was based on previous studies with small animals, which demonstrated the pharmacological effect of the drug [26,27], and is equivalent to 35 mg in a 70 kg human [25].…”
Section: Methodsmentioning
confidence: 99%